القراءة المعاصرة للسنة النبوية " محمد شحرور أنموذجا - بلعمري, أكرم (جامعة الوادي University of Eloued, 2016)
يستجلي هذا الموضوع قراءة معاصرة للسّنة النّبوية عند محمّد شحرور من خلال تتبّع أهمّ الرّؤى التّي يطرحها في كتاباته، خاصّة كتابه" السّنّة الرّسولية والسّنّة النّبوية"، باعتباره خلاصة آرائه تجاه السّنّة النّبوية، من خلال نقده للمفاهيم المسلّم بها، كوحيية السّنّة وحجيّتها ومفهومها وأقسامها وعدالة الصّحابة، ووضعه بدائل لقراءة السّنّة قراءة تليق بها، وهذا البحث محاولة جادة لمناقشة بعض هذه الآراء في هذه الورقات. ABSTRACT: this articles shows a Contemporary Reading of the Prophetic Sunnah According to the writings of Mohammad Shahrour Especialy in his book: "messenger traditions and prophetic Sunnah", As a Conclusion of his opinions Toward the Sunnah, Through his critique to :-The sunna as revelation Authoritatively of sunnah Fairness of companions And He put Other alternatives to read the sunna This research is a serious attempt to discuss Some of these opinions.
Contemporary Reading Of The Prophetic Sunnah Mohammad Shahrur As Example
Keywords: السّنّة، الوحي، النّبي، الرّسول، القراءة، النقد; Tradition- revelation- prophet – messenger-reading- criticism